Ceropegia sahyadrica Ansari Et Kulkarni-a New Species of Asclepiadaceae from Sahyadri Ranges in Maharashtra State - Ansari, M. Y.; Kulkarni, B. G. (Indian Forester, 1971)
Ceropegia sahyadrica Ansari et Kulkarni sp. Nov. collected from Poona and Ratnagiri districts (Maharashtra State) is described with illustrations. Earlier, this species had been misunderstood to be C. lawii Hook. F. and C. panchganiensis Blatt. Et McC. And, therefore, remained misidentified.